EFEKTIFITAS DAKWAH DALAM MENGEMBANGKAN KOGNITIF–FUNGSIONAL AUDIENS:SUATU PENDEKATAN PSIKOLOGI SOSIAL - Ihsan, Muhammad Alim (Hunafa: Jurnal Studia Islamika, 2010)
Islamic propagation (da’wah) can be regarded as effective if it is accepted by wider audiences and leads to fundamental changes of their religious attitude and behavior. At the individual level, it is refelected in the extent to which audiences undergo basic changes in their understanding of the core of Islamic teaching such as belief, ethics, worship and social relations. At the social level, it is reflected in a social milieu in which Islamic values illuminate social intercourse between communities.Kata Kunci: efektifitas dakwah, metode dakwah, kognisi, emosi, audiens